(untitled) (Fiep Bulletin - online, 2015)
Introduction: Adopting an active lifestyle is physically able to provide change of behavior of individuals. Moreover, changes in the environment provides, by creating suitable spaces for physical activity and information from a qualified professional. OBJECTIVES: Stipulate parameters of knowledge, sources of information from which this public uses for the practice of the exercises, determine the frequency and method of use of the equipment and thus estimate the possible risks that this population is exposed to perform activities without guidance. METHODS: A group of eighteen residents of the city of Camboriu, was approached from the response to a questionnaire, an epidemiological survey was carried out so as to determine the degree of knowledge and information about this practice exercise. Inclusion criteria included being a resident of the city of Camboriu, of both sexes, regularly attend the outdoor gym for at least a month, and have signed the consent form. Already exclusion criteria, the fact that a cognitive and / or mental deficit and not be present on site during data collection. RESULTS: According to the analysis of the questionnaire, we determined percentages for each question, and identify favorable and harmful points for participating public. CONCLUSION: The epidemiological profile was quite diverse. The lack of information for practitioners who perform activities empirically been shown, however great interest of these was observed in physical activity in pursuit of health promotion. It is believed that because the outdoor gyms are a novelty, the theoretical framework has been scarce.